Social Work Preparation to Compete in Today's Scientific Marketplace. (March 2017) - Nurius, Paula S.
As the scientific marketplace rapidly evolves, we must keep revisiting strategic preparation of our doctoral students and early career scholars to be successful innovators in these contexts. As an inherently integrative, change-oriented, community-engaged, and context-sensitive discipline, social work has enormous potential as a value-added partner for greater cross-fertilization among scientists and stakeholders not only from the academy but also from clinical settings, laboratories, industry, and systems leadership. Yet social work researchers not uncommonly encounter perception challenges as they strive to bring their scientific potential and wares to the marketplace. This article argues that innovation and impact are now central expectations of research. Current research priorities increasingly require teams to function at a transdisciplinary level of theoretical and methodological integration and to develop translational partnerships. The article concludes with thoughts on educational directions to better prepare our T-shaped emerging scholars to be perceived and function as value-added research innovators.